Efficacy of App-Based Yoga of Immortals Meditative Interventions on the Mental Health of Global Population During COVID-19 Pandemic - SHIVANAND, ISHAN (Digital Repository of Theses, 2024)
Amidst the unprecedented challenges posed by the COVID-19 pandemic, mental health issues such as depression, anxiety, and sleep disturbances became pervasive concerns. These issues surged due to heightened stressors and limited access to traditional support systems. Consequently, there has been a pressing need for flexible, home-based meditative interventions that could effectively address and mitigate their escalation. Thus, the problem addressed in this study was how mobile application-based Yoga of Immortals (YOI) meditative interventions can be utilized to improve the mental health of global population during COVID-19. The purpose of this double-blind mixed-method study was to investigate the efficacy and feasibility of YOI meditative modalities in mitigating the symptoms of depression, anxiety, and insomnia. For the study, a total of 1,505 participants (mean age 35.6 years, 40 % male and 60% female) were recruited and engaged with the YOI app for 8 weeks. Three validated questionnaires—the Patient Health Questionnaire (PHQ-8), the Generalized Anxiety Disorder questionnaire (GAD-7), and the Insomnia Severity Index (ISI)— were completed by 1,297 participants at four intervals: before starting, twice during usage (at the 4-week mark and 6-week mark), and once after the 8-week period. A control group of 590 individuals (mean age 34.9 years, 45 % male and 55% female) completed the same questionnaires without using the YOI app, serving as a comparative reference. YOI users experienced significant reductions in depression and anxiety symptoms. PHQ-8 scores dropped by an average of 50%, GAD-7 by 40–50%, and ISI by 50% compared to baseline. These changes were notably greater than those in the control group (p < 0.05). Particularly, participants with prior depression and anxiety diagnoses showed more significant decreases in PHQ-8 and GAD-7 scores (p < 0.05) than those without such diagnoses. Consistent YOI app use across 8 weeks substantially reduced depression, anxiety, and insomnia symptoms, indicating its potential as an effective intervention. YOI could serve as a valuable resource in addressing mental health challenges during and beyond the pandemic, especially for individuals with pre-existing mental health conditions. Future research could focus on evaluating YOI’s long-term effects on health with a detailed demographic analysis.